Investigations of E-Learning Patterns
DOI: 10.4018/978-1-60960-144-7.ch007
|View full text |Cite
|
Sign up to set email alerts
|

Embedding Design Patterns in a Methodology for a Design Science of E-Learning

Abstract: The discourse of research and practice in e-learning has been dominated by two extremes. On one hand, ethereal abstractions, which provide sound principles but do not lend themselves to implementation. On the other hand, detailed anecdotes which provide fascinating insights but pose a challenge to generalization. The void in between these two extremes calls for representations which capture transferable and modular elements of design knowledge.Design patterns originated as a form for democratizing design knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…conducting iterative cycles of testing and refining theories and solutions in practice; reflecting on producing theories and design principles and emphasizing solution implementation; and, finally, refining theories, problems, solutions and design principles. Figure 1 is said to be adapted, since it is a free translation by the authors in which references were added in respect of the development, production and refinement of theories -concepts that are present elsewhere in the literature (Bell, 2004;Brown, 1992;Collective, 2003;Collins, 1992;DiSessa & Cobb, 2004;Mor, 2011;Wang & Hannafin, 2005), and in which a loop required for the development of our solution was added between steps 2 and 3. Reeves (2006)) and Those of the Unified Process (Larman, 2004) For the development of the system prototype, the Unified Process (UP) (Larman, 2004) was used as a basis for the work, since it encompasses recognized and exemplary practices.…”
Section: Methodological Frameworkmentioning
confidence: 99%
“…conducting iterative cycles of testing and refining theories and solutions in practice; reflecting on producing theories and design principles and emphasizing solution implementation; and, finally, refining theories, problems, solutions and design principles. Figure 1 is said to be adapted, since it is a free translation by the authors in which references were added in respect of the development, production and refinement of theories -concepts that are present elsewhere in the literature (Bell, 2004;Brown, 1992;Collective, 2003;Collins, 1992;DiSessa & Cobb, 2004;Mor, 2011;Wang & Hannafin, 2005), and in which a loop required for the development of our solution was added between steps 2 and 3. Reeves (2006)) and Those of the Unified Process (Larman, 2004) For the development of the system prototype, the Unified Process (UP) (Larman, 2004) was used as a basis for the work, since it encompasses recognized and exemplary practices.…”
Section: Methodological Frameworkmentioning
confidence: 99%
“…The fact that they do not define the educational challenge and design the intervention tool themselves from the start, does not fit the ideal situation for inquiry based learning (Mor 2010;Anastopoulou et al 2012) but it does involve teachers, who state they do not have the time to invest in full research activities, in the process of implementing a new design, test it and consequently become involved in the second cycle of "devising new practices, plans of activity, resources and tools aimed at achieving particular educational aims in a given situation" (Mor and Craft 2012). In our case study teachers showed various signs of professional development.…”
Section: Discussion and Further Researchmentioning
confidence: 99%
“…A good way to formalize teacher's needs is to use a pattern-based approach. A pattern-based formalization, considering its semi-structured data, allows teachers-designers to express their pedagogical needs without extensive loss of semantic information while representing their pedagogical intention with a pattern-based editing tool [26] [27]. Then, we suggest creating pedagogical scenario that defines an orchestrated sequence of learning activities within this formalism.…”
Section: Proposition Of An Engineering Process Teacher-oriented: Frommentioning
confidence: 99%